SYSTEM COMPLEXITY INDEX - Vadim A. Kokhanovskiy; Marianna K. Sergeyeva; Manana G. Komakhidze (Advanced Engineering Research, 2012)
A new technique for the objective assessment of the engineering system complexity is offered. The complexity class concept is introduced.